Morphology, patterns and processes in the Oyster Bay headland bypass dunefield, South Africa - Elkington, Lauren (Rhodes University, Faculty of Science, Department of Geography, 2013)
Studies of the dunefield systems crossing the Cape St. Francis headland in the Eastern Cape have focused on the role that wind plays in sediment transfer in coastal dunefield systems, with limited consideration of the role of water. The aim of this study was to improve understanding of the morphology, processes and patterns within the Oyster Bay HBD system, focussing particularly on surface water and groundwater interactions and the role of surface water in sediment transfer across the dunefield system. An extensive field survey was conducted, to collect related data, complimented by spatial and temporal analysis of the study area using GIS. The key findings from this research were the apparent differences between the western and eastern regions of the dunefield with regard to specific drivers and the respective processes and responses. Wind is the major driver of change up to and across the crest of the dunefield. In the eastern region water (ground water, surface water and the Sand River System) is the primary agent of sediment flux through processes of aggregation and slumping as well as episodic events including debris flows. This study has highlighted a need for further quantitative studies that investigate the movement of sediment through dunefield systems such as this (where water is at or near the land surface). The paradigm that sediment flux is entirely due to wind is almost certainly simplistic, and deeper understanding of these systems is needed.
Keywords: Uncatalogued